The Concept of Insecurity within Latin American Campaigns. The PRO in Buenos Aires City as a Case Study (2007-2011) - Calzado, Mercedes; Lio, Vanesa; Fernández, Mariana (Mediaciones Sociales, 2015)
Since 2008, urban safety and crime have been considered as the main social issue by Latin American citizens. As a consequence, the battle against the phenomenon of urban insecurity became one of the most used governmentality strategies and political campaigns were focused around discourses of insecurity and fear. This paper aims to identify, from a case study, some political communication variables in the context of the security societies. To do so, a set of communication pieces from Buenos Aires City’s governing party 2007 and 2011 campaigns were analyzed. What kind of subjectivity is promoted? How is designed the role of the State? How is the security described? Which characteristics allow describing the citizen as a victim? Guided by the former questions, this paper investigates about modes of interpellation to citizenship, the enunciation of safety characteristics and the image assumed by the State during election times.
Keywords: political communication; security; victimization; government; case study.